1993
DOI: 10.1177/000456329303000216
|View full text |Cite
|
Sign up to set email alerts
|

Serum Glycated Albumin Concentrations during Pregnancy

Abstract: Additional key phrases: diabetes mellitus; haemoglobin Ale; glycated protein; fructosamineMany studies have been shown that fetal malformation and abnormal growth are significantly increased in pregnancies with poorly-controlled diabetes mellitus and that intensive glycaemic control is required in diabetic pregnancy. 1 Various indices including haemoglobin Ale, glycated protein and fructosamine are reported to be useful for assessing glycaemic control during pregnancy.t-' Glycated protein and fructosamine refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
2
8
0
Order By: Relevance
“…In this study, GA levels strongly correlated with the A1C levels in both GDM and NGT women and these glycated proteins also correlated with FPG and PPG, similar to the observation of Yang et al and Abe et al [10,12]. Hashimoto K et al [14] documented that A1C but not GA was elevated because of iron deficiency anemia in late pregnancy in diabetic women.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, GA levels strongly correlated with the A1C levels in both GDM and NGT women and these glycated proteins also correlated with FPG and PPG, similar to the observation of Yang et al and Abe et al [10,12]. Hashimoto K et al [14] documented that A1C but not GA was elevated because of iron deficiency anemia in late pregnancy in diabetic women.…”
Section: Discussionsupporting
confidence: 90%
“…To understand the glycemic excursions during pregnancy besides performing the point of care by capillary blood glucose measurement with glucometers, there is a need to have a test which could give an idea about the plasma glucose excursions in the previous weeks. GA as well as A1C are useful markers of glycemic control in the recent past [12]. GA reflects the retrospective glycemic excursions in the immediate past of approximately two weeks and A1C, glycemic excursions of more than eight weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, blood glucose levels need to be controlled more strictly during pregnancy than non-pregnancy. Because GA reflects the recent glycemic control status more sensitively than HbA1c [11], it could be a useful marker for management in diabetic pregnant women [12]. More recently, an enzymatic method for GA measurement [8] has been developed for use in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol levels are known to be inversely related to thyroid function (26), although in pregnant women, increased cholesterol levels and increased thyroid function have been reported to occur (7). Conflicting observations have been reported for serum glucose levels in women during pregnancy (1,35,45). Chiang et al (9) reported that glucose levels increased in the first trimester (organogenesis) from nonpregnant levels and decreased slightly throughout gestation thereafter.…”
Section: Methodsmentioning
confidence: 99%